2023
DOI: 10.1038/s41408-023-00784-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary malignancies in patients with chronic lymphocytic leukemia: a population-based study in the Netherlands, 1989-2019

Abstract: The longevity of patients with chronic lymphocytic leukemia (CLL) has improved progressively over the past decades, making it essential to understand long-term health outcomes, such as second primary malignancies (SPMs). Therefore, this nationwide, population-based study assessed the risk of SPM development in CLL patients diagnosed during 1989-2019 in the Netherlands compared to the expected number of malignancies in an age-, sex-, and period-matched group from the general Dutch population. In 24,815 CLL pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
(54 reference statements)
2
13
1
Order By: Relevance
“…27,28 We assessed the association between 5-year-periods of CLL A multivariate analysis revealed increased risk of SHM in CLL patients with male sex, younger age at diagnosis, and exposure to chemotherapy, consistent with prior studies. 13,16,21 In alignment with prior studies, we noted development of SHM significantly reduces OS in CLL patients (OS: 99 vs. 127 months). 11,12,29 Among myeloid SHM, CML (95 months) had the best while de-novo AML (63 months) had the poorest median OS after CLL diagnosis, a finding consistent with prior studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…27,28 We assessed the association between 5-year-periods of CLL A multivariate analysis revealed increased risk of SHM in CLL patients with male sex, younger age at diagnosis, and exposure to chemotherapy, consistent with prior studies. 13,16,21 In alignment with prior studies, we noted development of SHM significantly reduces OS in CLL patients (OS: 99 vs. 127 months). 11,12,29 Among myeloid SHM, CML (95 months) had the best while de-novo AML (63 months) had the poorest median OS after CLL diagnosis, a finding consistent with prior studies.…”
Section: Discussionsupporting
confidence: 87%
“…The risk is higher compared to that reported in prior studies, perhaps due to relatively recent period of CLL diagnosis (year 2000 onwards) included in our study than the prior studies (year 1973 onwards). 13,21 There has been a paradigm shift in treatment for CLL in this period and there is a growing concern for associated increment in second aggressive malignancies. During this period studies have reported higher risk of SHM in CLL survivors, partly attributable to fludarabine-based chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is associated with significant immunosuppression, which is thought to increase the risk for second primary neoplasms. Van der Straten, et al [ 12 ] reported an increase of more than two-fold in the risk for secondary cSCC among 25,000 CLL patients, compared to the general population. Patients with CLL also exhibit an eight-fold increased risk for non-melanoma skin cancers compared to the general population [ 13 ].…”
Section: Introductionmentioning
confidence: 99%